High expectations - Films for the Humanities (Firm); Agency for Instructional Technology (Princeton, NJ : Films for the Humanities & Sciences, 2004)
Documents the impact of high expectations on student mastery of basic and higher-level skills. Discusses the supportive effect of a positive school culture, the use of monitoring as a medium to communicate a school's insistence on academic excellence, and a dedication on the part of educators to develop challenging instruction
DVD Format
Keywords: Education -- Aims and objectives; Academic achievement; Curriculum planning; Films for the hearing impaired